RESEARCH ON THE INFLUENCE OF LANGUAGE CONTACTS ON TURKIC LANGUAGES: HISTORY AND CLASSIFICATION (Scientific journal of the Fergana State University, 2025)
In this article, a comprehensive study of the impact of language contact on the formation and development of Turkic languages is presented. The aim of the research is to identify mechanisms of borrowing and the influence of various linguistic systems on the morphological, syntactic, and phonetic structures of the Turkic language family. To achieve this, comparative-historical analysis, content analysis of empirical data, and modern computer-assisted linguistic methods are employed, integrating classical approaches with innovative research technologies. The study is based on an extensive review of domestic and international literature, including classical works and contemporary publications reflecting the influence of Mongolian, Iranian, Slavic, Chinese, and other languages on Turkic languages. The results demonstrate that language contacts play a key role in the dynamic evolution of the Turkic linguistic system, contributing to the emergence of new dialects, changes in lexical bases, and the adaptation of grammatical constructions under external influences. The conclusions underscore the need for further interdisciplinary studies to deepen our understanding of language formation processes in the context of globalization and cultural heritage preservation, thereby strengthening national identity and promoting intercultural dialogue. These findings provide a basis for developing new methodological approaches in linguistics.